PENGUNGKAPAN INOVASI DISRUPTIF INDUSTRI PERBANKAN INDONESIA - Djoko Suhardjanto; Agung Nur Probohudono; Indrian Supheni (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
Voluntary disclosure is corporate communication to the broader public than disclosures required by capital market regulations. The disclosure of information is beneficial as a consideration in making decisions. The Disruptive innovation disclosure is a voluntary disclosure that provides information about the state of extraordinary innovation in the company. Disruptive innovation is used to describe revolutionary innovations and not evolutionary innovations (Thomond and Lettice, 2002). Outstanding innovation to expand, develop new markets and provide new functions, affecting existing market relationships. This research is critical to know the company's adaptive capacity, going concern, sustainability, and value creation. This study examines whether financial capital, human capital, and organizational capital affect the disruptive innovation disclosure. This quantitative study uses data from banking financial services companies listed on the IDX from 2015 to 2019. There are 205 data observations observed—processing and data analysis using OLS regression. Additional analysis performed was the ANOVA difference test. The results showed that the level of disruptive innovation disclosure was 30.96%. The disclosure story is low and means that adaptive and innovative power is critical in the highly competitive banking industry. Financial capital, human capital and organizational capital have a significant positive effect on the disruptive innovation disclosure.